2024
DOI: 10.1136/bmjdrc-2023-003548
|View full text |Cite
|
Sign up to set email alerts
|

Incident dementia risk among patients with type 2 diabetes receiving metformin versus alternative oral glucose-lowering therapy: an observational cohort study using UK primary healthcare records

William Doran,
Louis Tunnicliffe,
Rutendo Muzambi
et al.

Abstract: Introduction4.2 million individuals in the UK have type 2 diabetes, a known risk factor for dementia and mild cognitive impairment (MCI). Diabetes treatment may modify this association, but existing evidence is conflicting. We therefore aimed to assess the association between metformin therapy and risk of incident all-cause dementia or MCI compared with other oral glucose-lowering therapies (GLTs).Research design and methodsWe conducted an observational cohort study using the Clinical Practice Research Datalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results from human studies have provided evidence that metformin prevents cognitive decline or dementia (Barbera et al, 2024;Doran et al, 2024). A cohort study utilizing UK primary healthcare records, involving 211,396 individuals, revealed that the use of metformin was linked to a reduced risk of dementia (adjusted HR = 0.86) and mild cognitive impairment (adjusted HR = 0.92) (Doran et al, 2024).…”
Section: Human Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from human studies have provided evidence that metformin prevents cognitive decline or dementia (Barbera et al, 2024;Doran et al, 2024). A cohort study utilizing UK primary healthcare records, involving 211,396 individuals, revealed that the use of metformin was linked to a reduced risk of dementia (adjusted HR = 0.86) and mild cognitive impairment (adjusted HR = 0.92) (Doran et al, 2024).…”
Section: Human Studiesmentioning
confidence: 99%
“…The results from human studies have provided evidence that metformin prevents cognitive decline or dementia (Barbera et al, 2024;Doran et al, 2024). A cohort study utilizing UK primary healthcare records, involving 211,396 individuals, revealed that the use of metformin was linked to a reduced risk of dementia (adjusted HR = 0.86) and mild cognitive impairment (adjusted HR = 0.92) (Doran et al, 2024). In a cohort study of 12,220 metformin users, including 12,220 early terminators and 29,126 routine users, discontinuation of metformin treatment was found to be associated with an increased incidence of dementia.…”
Section: Human Studiesmentioning
confidence: 99%